UTILIZATION OF CORK COCOPEAT AS A COMPOSITE SILENCER - Eko Yohanes Setyawan; Totok Sugiarto; Soeparno Djiwo (Widyagama University of Malang, 2018)
Noise is unwanted sound of activity in a particular time and levels that can cause health problems and environmental comfort. Sound or sound is heard as the stimulation on the auditory nerve cells in the ear by a wave of longitudional caused the vibration of the sound or sound source and the waves propagate through the medium of air or any other conductor. Threshold noise received by normal human beings that is 85 dB, when the normal threshold above can lead to damage to the auditory system when not using protective tools in conducting activities. The noise can be avoided by way of designing construction work. In addition noise can be minimised with soundproofing materials. During this suppressor used i.e. from rubber, plastic and metal, but the materials used nowadays are not yet are biodegradable. Therefore, to minimize noise with materials that are biodegradable with composite materials. One effort in selecting materials that are biodegradable with coconut plant utilization have been known by the wider community wastes a lot of cocopeat i.e. we encounter in a craftsmen coir because its existence is underutilized by craftsmen. Natural fibers are biodegradable they have opportunities to be developed further into a composite reinforcement materials that have high performance as an alternative replacement of artificial fiber materials based compounds, hydrocarbons or metal.Methods used i.e. experimental methods, with chemical treatment of cocopeat aims to separate dirt and the lignin contained in the cocopeat so cocopeat can bind matrix that would have a high performance in the muffle the sound so that it can reduce noise. After treatment with alkali, creating a noise test specimens in accordance with the design of the mold. Then the noise testing was performed using a sound pressure level to know the ability of mute and SEM photographs to find causal in a composite able to absorb sound.The results showed, the percentage composition of the powder of coconut fibres (cocopeat) have an influence in absorbing sound. In this study the composition of the powder of coconut fibres (cocopeat) 60% has a high sound absorbency. Desible votes after going through the composite powder coconut fibres 60% has a value of 102.73 db at a distance of 50 cm, 100 db at a distance of 91.57 cm and 80.23 db at a distance of 150 cm. And sound absorbency coefficient on the composition of the powder of coconut fibres 60% has a value of 0.144 on a distance of 50 cm, 100 cm at a distance of 0.237 and 0.331 approximately 150 cm. Whereas in terms of surface morphology of SEM photo of that on the composition of the powder 60% coconut fibers have more porosity percentage which has absorption ability voice more effectively so that the sound after passing the composition of composite lower. Keywords: noise, Biodegradable Composite, cocopeat, SEM.